Evolution - Barton, Nicholas H; Briggs, Derek E G; Eisen, Jonathan A; Goldstein, David B; Patel, Nipam H (New York : Cold Springer Harbor Laboratory Press, 2007)
Evolution is a new book on evolutionary biology that integrates molecular biology, genomics, and human genetics with traditional studies of evolutionary processes. Recommended as a primary textbook for undergraduate courses in evolution Required reading for biologists seeking a clear, current, and comprehensive account of evolutionary theory and mechanisms Written by experts in population genetics, bacterial genomics, paleontology, human genetics, and developmental biology Integrates molecular and evolutionary biology in ways that reflect current directions in research
Includes bibliographical references.; Glossary 783-801p.; Index 811-833p.
Keywords: Evolution-textbooks.